"Inclusive Entrepreneurship": A Process for Improving Self-Employment for People with Disabilities. Issue 1 (2nd April 2016) - Shaheen, Gary E.
ABSTRACT: This article describes the theoretical framework, processes, and outcomes associated with a U.S. Department of Labor, Office of Disability Employment Programs (ODEP)-funded project: "Start-UP NY." Beginning in 2007, ODEP funded three Start-UP projects throughout the United States to test and demonstrate improved practices supporting entrepreneurship among people with diverse disabilities, including those with mental illnesses and veterans with disabilities. The New York project coined the term "Inclusive Entrepreneurship" to describe a model that promoted change at the individual, program, and systems level to improve the rate of small business development by people with disabilities. The author describes the genesis of the project, its intended effects and the lessons learned along the way that resulted in either course corrections or improvements, He then discusses how the project has been sustained and provides recommendations for replicating the project's approach and methods in other United States communities or in other countries.